2021
DOI: 10.26464/epp2021024
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Large-Scale Solar Wind Events in the Outer Heliosphere From a Numerical MHD Simulation

Abstract: Voyager 1 occasionally detected the sudden jumps of the local interstellar magnetic field strength since its heliopause crossing in August 2012. These events were believed to be associated with the outward propagating shocks that had the solar wind origin in the inner heliosphere. Here we investigate the correlation between the interstellar shocks and the large-scale solar wind events by means of the numerical MHD simulation. The solar wind is simplified as a symmetric flow near the equatorial plane, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 2017 ; Guo et al. 2021 ). These recent models have the advantage of including the termination shock, heliosheath and heliopause, but face difficulties such as how to determine the 3D solar wind input, and reproduce correct locations of the heliospheric structures and precise timing with the Voyager 1 measurements.…”
Section: The Lismmentioning
confidence: 99%
“… 2017 ; Guo et al. 2021 ). These recent models have the advantage of including the termination shock, heliosheath and heliopause, but face difficulties such as how to determine the 3D solar wind input, and reproduce correct locations of the heliospheric structures and precise timing with the Voyager 1 measurements.…”
Section: The Lismmentioning
confidence: 99%
“…For better comparison, the positions of New Horizons, Voyager 1 and 2 are marked in the figure. These three spacecrafts are assumed to move upwind toward the intestellar neutrals, which is roughly consistent with the reality (Guo et al, 2021). Note that Voyager 1 is approaching the heliopause which is located at 121.6 AU from the later observation, the termination shock is at about 81 AU at the time.…”
Section: Numerical Modelmentioning
confidence: 57%
“…Richardson et al (2017) found that the pressure pulses detected by Voyager 2 in the heliosheath are correlated with the interstellar shocks by Voyager 1. Based on a spherically symmetric MHD model containing termination shocks, Guo et al (2021) performed the numerical simulations using three solar wind sources (STEREO A and B, and OMNI) with different longitudes as inner boundary conditions, and did comparison analyses with the in situ observations of New Horizons, Voyager 1 and 2 in the outer heliosphere. Their results indicate the possible connection between the pressure pulse observed by Voyager 2 and the interstellar shock events observed by Voyager 1.…”
mentioning
confidence: 99%
“…Recently, Guo et al. ( 2021 ) extended their 1-D numerical MHD model by using inputs from OMNI, STEREO-A, and B at 1 AU and found that each of the plasma oscillations and shock events in the VLISM are linked to large-scale solar wind events. An observational study by Richardson et al.…”
Section: Shocks In the Vlismmentioning
confidence: 99%